Multimedia Interaktif Berbasis Literasi Numerasi Berbantuan Android untuk Materi Pembagian Kelas IV - Ratnasari, Ni Made Manika; Wiarta, I Wayan; Sujana, I Wayan (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aims to be motivated by the learning outcomes of class IV students at SD Number 4 Darmasaba in the distribution material which is classified as unsatisfactory, students have not achieved the expected learning outcomes. The development of interactive multimedia was chosen as a solution to mathematics learning problems, especially in distribution material for class IV because it was based on the results of an analysis of the needs of students and educators carried out in the field, namely at SD Number 4 Darmasaba. This research uses the ADDIE model (analyze, design, development, implementation, evaluation). The data collection methods used in this research are observation, interviews, questionnaires and tests. The data collection instruments used in the development of interactive multimedia based on Android-assisted numeracy literacy for class IV division material at SD Number 4 Darmasaba are questionnaires and tests. Based on the results of effectiveness tests that have been carried out, interactive multimedia based on Android-assisted numeracy literacy is effectively used for class IV division materials at SD Number 4 Darmasaba